(untitled) (European Journal of Education, 2022)
The focus of this research was to look into the information security awareness of Chinese university students during the COVID-19 pandemic and make recommendations based on the survey's findings and research literature. The quantitative method is applied in this study. 111 Chinese college students were randomly sampled and requested to answer a Likert information security awareness questionnaire. The descriptive analysis of the data in this study is also done with SPSS. The findings revealed that the vast majority of college students know the significance of information security awareness and have basic information security awareness, based on the data collected.However, some students have not participated in relevant training courses, and many college students do not pay enough attention to personal information security, resulting in poor performance in areas such as files and passwords. As a result, effective solutions such as information security training projects are required to address the current deficiencies. The findings of this study have implications for university administrators and policymakers in terms of how to raise students' awareness of the security of their online learning information. The study should use mixed methods and large sample sizes in the future to provide more detailed and comprehensive survey data, and more credible evidence of college students' information security awareness.